Postpartum contraception: determinants of intention and methods of use among an obstetric cohort in a tertiary hospital in Jos, North Central Nigeria - Ujah, Otobo I.; Ocheke, Amaka N.; Mutihir, Josiah T.; Okopi, Joseph Anejo; Ujah, Innocent A. O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Postpartum contraception reduces the risk of unintended and rapid repeat pregnancies. A comprehensive postpartum family planning (PPFP) service can enable women make adequate and informed choices on a preferred contraceptive method, initiating a method as well as encouraging them to use that method for a period depending on their reproductive intentions. Methods: This study aimed to determine women’s intention regarding uptake of postpartum family planning, the preferred methods and the factors associated with uptake. We conducted a cross-sectional study among women attending antenatal and postnatal clinics at the Jos University Teaching Hospital, Jos, Nigeria using structured questionnaires. Data was analyzed using descriptive statistics and chi square test of comparison. Results: Four hundred and five women participated in the study. The mean age of the respondents was 28.4+5.3 years. The previous contraceptive usage was 39.8%. A total of 262 (64%) women intend to use a method of postpartum contraception. The most preferred intended postpartum contraceptive was subdermal implant (19.2%) followed by injectables (18.4%) and intrauterine contraceptive device (14.7%). Reasons cited for nonuse of postpartum contraception include spousal refusal, effect on fertility, desire for further child bearing, religious beliefs. Conclusions: Counselling on postpartum contraception during the antenatal and postnatal period can help women make informed choices among the wide range of available contraception.